2021
DOI: 10.3390/healthcare9121758
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Glandular Dose between Full-Field Digital Mammography and Digital Breast Tomosynthesis

Abstract: Early detection of breast cancer is diagnosed using mammography, the gold standard in breast screening. However, its increased use also provokes radiation-induced breast malignancy. Thus, monitoring and regulating the mean glandular dose (MGD) is essential. The purpose of this study was to determine MGD for full-field digital mammography (FFDM) and digital breast tomosynthesis (DBT) in the radiology department of a single centre. We also analysed the exposure factors as a function of breast thickness. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A study by Gennaro et al (2018) concluded that the average increase of DBT dose compared to FFDM was 38%, and a range between 0 % and 75% [ 7 ]. Although another study by Teoh et al (2021) found dose in DBT was slightly higher than in FFDM, in CC projection, AGD of FFDM showed somewhat higher than DBT [3.37 mGy vs. 1.86 mGy] and vice versa in the MLO view [1.37 mGy vs. 1.88 mGy] [ 28 ]. The high dose observed in DBT compared to FFDM is primarily due to the technology of DBT.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gennaro et al (2018) concluded that the average increase of DBT dose compared to FFDM was 38%, and a range between 0 % and 75% [ 7 ]. Although another study by Teoh et al (2021) found dose in DBT was slightly higher than in FFDM, in CC projection, AGD of FFDM showed somewhat higher than DBT [3.37 mGy vs. 1.86 mGy] and vice versa in the MLO view [1.37 mGy vs. 1.88 mGy] [ 28 ]. The high dose observed in DBT compared to FFDM is primarily due to the technology of DBT.…”
Section: Discussionmentioning
confidence: 99%
“…Mammography represents the gold standard for breast cancer screening and early diagnosis. However, toxicity induced by the use of radiation and the risk of radiation-induced cancer in young women is not negligible [23]. Colonoscopy, strongly recommended for early colorectal cancer detection, is an invasive examination that can be burdened by severe complications, such as bowel perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in technology have introduced reconstruction algorithms that directly generate 2D synthetic mammography (2DSM) images from the DBT dataset, which are comparable in diagnostic performance to FFDM and do not require additional radiation exposure [18,19]. Therefore, it is crucial to evaluate radiation doses and risks associated with mammographic examinations to determine the benefits of such exams [20]. It is also essential to analyze recall rates and the relationship between various mammographic parameters, such as compressed breast thickness (CBT), exposure factors, and target/filter combination of DBT and DM, to optimise the radiation dose.…”
Section: Introductionmentioning
confidence: 99%